DESCRIPTION OF STRESS LEVEL IN PARENTS WITH CHILDREN WITH DISAPPEARANCE - Andini, Fadya Putri; Maemonah, Siti (Global Ten Public Health and Nursing Journal, 2023)
The existence of children with special needs in the family will be a separate stressor for each family member because it can be a burden on the family both mentally and materially, stress for parents is a form of process that results in psychological and physiological reactions that are not good that come from having to fulfill obligations as a person. old. The purpose of this research is to find out the stress level of parents who have mentally retarded children at SLB-AC Dharma Wanita Sidoarjo.This type of research is descriptive research using a questionnaire using a Depression Anxiety Stress measuring instrument questionnaire (DASS 42) filled in by parents of students of SLB-AC Dharma Wanita Sidoarjo. This research was conducted with a cross sectional approach and found 46 parents as a sample.The results of this study found that the stress level of parents who had mentally retarded children was obtained by some parents experiencing mild stress as many as 10 people (22%), parents who experienced moderate stress as many as 4 people (8%) and some parents who did not experience stress as many as 32 people ( 70%). From the results of this study, it can be concluded that almost all of the parents of SLB-AC Dharma Wanita Sidoarjo, only a few people experienced mild stress and none experienced severe stress. The existence of children with special needs in the family will be a separate stressor for each family member because it can be a burden on the family both mentally and materially, stress for parents is a form of process that results in psychological and physiological reactions that are not good that come from having to fulfill obligations as a person. old. The purpose of this research is to find out the stress level of parents who have mentally retarded children at SLB-AC Dharma Wanita Sidoarjo.This type of research is descriptive research using a questionnaire using a Depression Anxiety Stress measuring instrument questionnaire (DASS 42) filled in by parents of students of SLB-AC Dharma Wanita Sidoarjo. This research was conducted with a cross sectional approach and found 46 parents as a sample.The results of this study found that the stress level of parents who had mentally retarded children was obtained by some parents experiencing mild stress as many as 10 people (22%), parents who experienced moderate stress as many as 4 people (8%) and some parents who did not experience stress as many as 32 people ( 70%). From the results of this study, it can be concluded that almost all of the parents of SLB-AC Dharma Wanita Sidoarjo, only a few people experienced mild stress and none experienced severe stress.